Reimagining Doctoral Mentoring: Toward the Development of Culturally Liberative STEM Faculty Doctoral Mentors - Cathy Howell; Marah Lambert; Edith Gnanadass; Lisa R Merriweather (Adult Education Research Conference, 2023)
Using anti-Black racism and critical capital theory, this paper highlights findings of a meta-analysis based on research products developed from a qualitative multiple embedded case study of STEM doctoral mentoring and argues for the development of culturally liberative doctoral mentorship.
Keywords: STEM doctoral mentoring; culturally liberative mentoring; critical capital theory; anti-black racism; mentoring and adult education